Increased Cerebrospinal Fluid S100B and NSE Reflect Neuronal and Glial Damage in Parkinson’s Disease - Papuć, Ewa; Rejdak, Konrad (Frontiers in Aging Neuroscience, 2020)
Introduction The diagnosis of Parkinson’s disease (PD) mainly relies on clinical manifestation, but may be difficult to make in very early stages of the disease, especially in pre-motor PD. Thus, there is great interest in finding a biomarker for PD. Among diagnostic biomarkers, the most promising molecules are those which reflect the pathophysiological mechanisms of the disease. Until now, only α-synuclein, a classical CSF Alzheimer’s disease biomarker, and neurofilament light (NFL) chain have turned out to be helpful in differential diagnosis between PD and healthy control subjects. Aim To assess whether CSF molecules related to some pathological processes present in PD might be of interest in the diagnosis of PD and whether they correlate with disease severity. Methods CSF levels of S100 B and NSE were measured in 58 PD patients and in 28 healthy control subjects. Correlations were determined between the levels of these CSF molecules and measures of disease severity (Hoehn-Yahr scale and UPDRS part III), as well as disease duration and levodopa dose. Results CSF S100 B and CSF NSE were both significantly increased in PD subjects vs healthy controls (p=0.007 and p=0.00035, respectively). CSF S100 B was significantly positively correlated with measures of disease severity (H-Y score and UPDRS part III), as well as disease duration (p<0.05). No correlation was found between CSF NSE levels and disease severity or disease duration (p>0.05). CSF S 100 B levels alone provided a relatively high discrimination (AUC 0.77) between PD and healthy controls, with 60.7% sensitivity and 88.5% specificity (p<0.001) at a cut-off value of 123.22 pg/ml. Similarly, CSF NSE levels alone provided a relatively high discrimination (AUC 0.775) between PD and healthy controls, with 78.6% sensitivity and 74.1% specificity at a cut-off value of 51.56 ng/ml (p<0.001). Conclusions Our results show that both CSF S100 B and CSF NSE seem to be promising markers of the axonal and glial degeneration present in PD. Additionally CSF S100 B may be a promising marker of PD progression.